KEANEKARAGAMAN JENIS TUMBUHAN PAKU (PTERIDOPHYTA) EPIFIT DI ARBORETUM UNIVERSITAS RIAU SEBAGAI RANCANGAN BUKU SAKU BERGAMBAR PADA MATERI KINGDOM PLANTAE DI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Epiphytic ferns are ferns that use their host tree as a place to live andaquatic ferns are ferns that can live in water. ta species of epiphytic ferns in thearboretum of the University of Riau can be seen from the enrichment materials forlearning media for students at school. Based on the survey results at SMA 10Pekanbaru, so far in the learning process, especially in the Kingdom Plantae materialcontained in KD 3.8 in class X. This research was carried out at the Arboretum of RiauUniversity, Bina Widya Campus Km. 12.5, Simpang Baru, Tampan District, PekanbaruCity from January to February 2021. To take an inventory of epiphytic ferns using asurvey method, namely the collection is carried out through direct observations in thefield to inventory data on types of epiphytic ferns at the Arboretum of Riau University.Sampling technique and documentation using cruise methods (cruise methods). Thesecond stage in the form of pocketbook design is done by analyzing the suitability of theresearch results with the applicable KD, then making a pocketbook design, and finallydeveloping the contents of the pocketbook so that research is conveyed well to students.At the Arboretum of the University of Riau, epiphytic ferns were found consisting of 5families with 10 species. The results of this study also turned out to be compatible withthe material in class X SMA so that this research can be used as a design for learningmedia in the form of a pocketbook which includes KD 3.8 and KD 4.8 for class Xdiscussing plantae. The material that can be achieved with this pocketbook includes thetypes and characteristics of ferns.Key Words: Arboretum, Pocket Book, Diversity, Epiphytic Nails.